2022
DOI: 10.4322/acr.2021.386
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Rubella Syndrome as a possible cause for persistent thrombocytopenia in early infancy: The Forgotten Culprit

Abstract: We present a case of a late preterm intrauterine growth-restricted neonate with isolated and persistent severe thrombocytopenia. At birth, the neonate did not have a complete clinical spectrum of congenital rubella syndrome (CRS) but later developed peculiar findings that helped clinch the diagnosis. The neonate also had interstitial pneumonia and died secondary to superimposed acute viral infection leading to acute respiratory distress syndrome. The serology was positive for IgM antibodies against the rubella… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Several studies have found the fact of cytokine storms in congenital rubella syndrome that cause a lot of multiorgan damage as evidenced by the findings of an immune system complex containing rubella virus antigens in systemically circulating serum (Frenkel et al, 2018;Sakuragi et al, 2022;Shukla & Maraqa, 2022). Cytologically, mononuclear inflamatoric infiltrates were found in several organs of the body of babies who died, especially in the brain and lungs (Kumar et al, 2022). In addition, advanced clinical manifestations in congenital rubella syndrome are also thought to be mediated by an immune response (Lee and Bowden, 2000).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have found the fact of cytokine storms in congenital rubella syndrome that cause a lot of multiorgan damage as evidenced by the findings of an immune system complex containing rubella virus antigens in systemically circulating serum (Frenkel et al, 2018;Sakuragi et al, 2022;Shukla & Maraqa, 2022). Cytologically, mononuclear inflamatoric infiltrates were found in several organs of the body of babies who died, especially in the brain and lungs (Kumar et al, 2022). In addition, advanced clinical manifestations in congenital rubella syndrome are also thought to be mediated by an immune response (Lee and Bowden, 2000).…”
Section: Resultsmentioning
confidence: 99%